Application of the NHT (Numbered Head Together) Learning Model to Improve Student Learning Outcomes at SDN 2 Sriwedari, Salaman, Magelang Regency for the 2020/2021 Academic Years - Uswatul Tri Utami (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study purpose to improve student learning outcomes by applying the NHT (Numbered HeadTogether) learning model with the research subjects of fifth grade students at Sriwedari 2Elementary School, Salaman District, Magelang Regency. The research method used is CAR(Classroom Action Assessment) and the form of data collection is a multiple choice test. In the firstcycle reached an average of 60.83. In the second cycle reached an average of 77.5. Based on this, itcan be concluded that the NHT model can improve learning outcomes, so the NHT model can beused as an alternative after finding problems regarding student learning outcomes.